Coping with cultural dissonance in study abroad: affective reactions and intercultural development - Méndez García, María del Carmen (Onomázein, 2023)
This paper investigates feelings and emotions in intercultural development through an analysis of students’ journals. It looks into the affective reactions to life in Spain and how these relate to the intercultural development of a cohort of 26 American students participating in a calendar year study abroad programme (SAP) in a Spanish university, a pertinent study given that Spain, which hosts 9,5% of total American students abroad, has become the third preferred destination of American university students (Institute of International Education, 2019). Although the literature on cultural dissonance highlights the prevalence of feelings of distress when sojourners are removed from their social support systems, findings divulge a myriad of feelings classified into 9 areas that show a balance between uncertainty and stress of study abroad (SA), and excitement and feelings of well-being. Departing from affective reactions, analysis has likewise been conducted on how students come to terms with a different reality. Data evince that understanding new meanings and symbols is done through a comparative/contrastive problematising orientation through which SA is presented as challenge rather than as threat. The paper concludes that SA and reflection upon it contribute to reassess and shift frames of reference, influencing intercultural development and personal growth.